2021
DOI: 10.1158/1078-0432.ccr-20-1830
|View full text |Cite
|
Sign up to set email alerts
|

OX40 Agonist BMS-986178 Alone or in Combination With Nivolumab and/or Ipilimumab in Patients With Advanced Solid Tumors

Abstract: This phase I/IIa study (NCT02737475) evaluated the safety and activity of BMS-986178, a fully human OX40 agonist IgG1 mAb, AE nivolumab and/or ipilimumab in patients with advanced solid tumors. Patients and Methods: Patients (with non-small cell lung, renal cell, bladder, other advanced cancers) received BMS-986178 (20-320 mg) AE nivolumab (240-480 mg) and/or ipilimumab (1-3 mg/kg). The primary endpoint was safety. Additional endpoints included immunogenicity, pharmacodynamics, pharmacokinetics, and antitumor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 42 publications
(62 reference statements)
3
38
0
Order By: Relevance
“…These results indicate that sequential, rather than simultaneous administration of OX40 agonists and anti-PD-1 can revert PD-1 resistance and improve responses to combination therapy. Consequently, one of the approaches in a Bristol-Myers Squibb (BMS) clinical study (39) involves exploring the effectiveness of sequentially administering an OX40 agonist, BMS-986178, anti-PD1 (Nivolumab), an allogeneic autophagosome-enriched vaccine, DPV-001 and cyclophosphamide in TNBC patients (ClinicalTrials.gov Identifier: NCT02737475). Another co-stimulatory molecule, the inducible co-stimulator (ICOS), is mainly expressed by activated CD4+ and CD8+ T cells and constitutively by Tregs.…”
Section: Stimulatory Checkpointsmentioning
confidence: 99%
“…These results indicate that sequential, rather than simultaneous administration of OX40 agonists and anti-PD-1 can revert PD-1 resistance and improve responses to combination therapy. Consequently, one of the approaches in a Bristol-Myers Squibb (BMS) clinical study (39) involves exploring the effectiveness of sequentially administering an OX40 agonist, BMS-986178, anti-PD1 (Nivolumab), an allogeneic autophagosome-enriched vaccine, DPV-001 and cyclophosphamide in TNBC patients (ClinicalTrials.gov Identifier: NCT02737475). Another co-stimulatory molecule, the inducible co-stimulator (ICOS), is mainly expressed by activated CD4+ and CD8+ T cells and constitutively by Tregs.…”
Section: Stimulatory Checkpointsmentioning
confidence: 99%
“…Preliminary data from this trial demonstrate that BMS-986178 as a monotherapy or combined with nivolumab and/or ipilimumab is well tolerated with no dose-limiting toxicities (DLTs) or discontinuation due to study treatment [ 79 ]. Although earlier data showed that BMS-986178 monotherapy resulted in increased proinflammatory cytokines and higher proliferation and activity of CD4 and CD8 T cells when combined with either anti-PD-1 or anti-CTLA-4 [ 96 ], this was not recapitulated in this trial upon interrogation of intratumoral or peripheral CD8 T cells [ 90 ]. Results obtained here suggest that the responses observed were not greater than what would have been projected for nivolumab or ipilimumab treatment alone.…”
Section: Third-generation Immunotherapy Combinationsmentioning
confidence: 77%
“…The tumor necrosis factor receptor superfamily (TNFRSF) contains many receptors responsible for the development, survival and function of immune cells, including OX40, CD40, FasR, 4-1BB, among others [ 84 ]. Studies interrogating the efficacy of monoclonal antibodies specific for costimulatory receptors, such as CD40 (dacetuzumab, CP-870,893 and lucatumumab [ 85 , 86 , 87 , 88 ]), OX40 (9B12 [ 89 ], BMS-986,178 [ 90 ]) and LAG3 (IMP321 [ 91 ]), are currently underway. Targeting these receptors with agonistic monoclonal antibodies could be beneficial in generating more robust antitumor immune responses.…”
Section: Third-generation Immunotherapy Combinationsmentioning
confidence: 99%
“…BMS-986178 is another fully human IgG mAb against OX40 assessed as monotherapy or in combination with nivolumab in advanced solid tumors. No anti-tumor activity was observed with monotherapy and overall response rate (ORR) was 6–12% in the combination cohort [ 39 ]. Overall, OX40 targeting monotherapy appears to be tolerable however, it does not induce durable anti-tumor responses.…”
Section: The Role Of Cd137 In the Tumor Microenvironmentmentioning
confidence: 99%